A History of Platform Mound Ceremonialism : Finding Meaning in Elevated Ground - Kassabaum, Megan C. (Book collections on Project MUSE., 2021)
"This book presents a temporally and geographically broad yet detailed history of an important form of Native American architecture, the platform mound, revealing unexpected continuities in moundbuilding over many thousands of years"--